How do you simplify #12-15sqrt6 + 8sqrt6 - 10sqrt36#?

2 Answers
Jun 20, 2016

Answer:

#-48-7sqrt(6)#

Explanation:

#12-15sqrt(6)+8sqrt(6)-10sqrt(36)#
#=12-15sqrt(6)+8sqrt(6)-10sqrt(6^2)#
#=12-15sqrt(6)+8sqrt(6)-10*6#
#=12-15sqrt(6)+8sqrt(6)-60#
#=12-60+(-15+8)sqrt(6)#
#=-48-7sqrt(6)#

Jun 20, 2016

Answer:

#-48-(7*sqrt(6))#

Explanation:

#12+(-15*sqrt(6))+(8*sqrt(6))+(-10*sqrt(36))#

We know that #sqrt(36)=6#.

So, #12+(-15sqrt(6))+(8*sqrt(6))+(-60)#.

#12-60=-48#

So, #-48+(-15sqrt(6))+(8*sqrt(6))#

Now, take out #sqrt(6)# from last two parenthesis.

That would give us #-48+(sqrt(6)*(-15+8))#

#-15+8=-7#

So, the answer would be #-48-(7*sqrt(6))#